PERBANDINGAN HASIL BELAJAR MATEMATIKA ANTARA PENGGUNAAN MEDIA BERBASIS KOMPUTER DAN CETAK - Fadila, Abi (JURNAL E-DUMATH, 2016)
This research aims to know whether there is difference between of the studentsachievement in math by using teaching media with instructional media basedcomputer and printed media (books). This research is experimental researchusing posttest-only control design. The population was all the of the first gradestudents at SMP Negeri 8 Bandar Lampung. The samples of the research weretaken by using the cluster random sampling technique. Data acquisition is doneby testing with data analysis techniques using t-test if the data distributionnormal and homoginity. The result of the research can be concluded that there isdifference between of the students achievement in math by using teaching mediawith instructional media based computer and printed media (books), and thestudents achievements in math by using teaching media with instructional mediabased computer was higher than the students achievements in math by usingteaching media with printed media (books).Keywords: instructional media based computer, printed media, studentsachievements in math